Construction of the annual macrocycle of short-distance runners at the stage of in-depth specialization - Kozhedub, M.S.; Godun, D.; Vrublevsky, E.P. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to improving the sports training of sprinters aged 15-17 years based on the analysis of the dynamics of their training loads and the ratio of work of various directions in the annual cycle. Methods and structure of the study. Variants of individual planning of year-round training were subjected to statistical analysis in 23 sprinters of the I sports category (n=18) and candidates for master of sports (n=5). The volume of fixed assets of training was fixed in specific units of measurement (kilometers, tons, number of times) and from the total annual volume, taken as 100%, the load dynamics by months of the annual training cycle was calculated as a percentage. Results and conclusions. On the basis of statistical analysis, the issues of organizing the training load and the ratio of work of various predominant directions in the structure of the annual cycle of training for sprinters of a given level of sportsmanship are considered. The nature and dynamics of the distribution of training means for athletes by months of the annual macrocycle were determined. The data obtained indicate that the modulation of the load parameters in terms of magnitude and direction, as well as the content and nature, should not only correspond to the strategic goals of training in the macrocycle, but also be commensurate with the natural course of development of the athlete’s motor function.